Historiography in the Twentieth Century : From Scientific Objectivity to the Postmodern Challenge - Iggers, Georg G. (Book collections on Project MUSE., 2005)
Intellectual historian Georg G. Iggers examines the profound changes in ideas about the nature of history and historiography. He faces the basic assumptions upon which historical research and writing have been based, and describes how the newly emerging social sciences transformed historiography following World War II.